VISCOELASTIC STRUCTURAL MODEL OF ASPHALT CONCRETE - Bogomolov, V.; Zhdanyuk, V.; Tsynka, A.; Богомолов, В. А.; Жданюк, В. К.; Цинка, А. А.; Богомолов, В. О.; Цинка, А. О. (Харьковский национальный автомобильно-дорожный университет, 2016)
The viscoelastic rheological model of asphalt concrete based on the generalized Kelvin model is offered. The mathematical model of asphalt concrete viscoelastic behavior that can be used for calculation of asphalt concrete upper layers of non-rigid pavements for strength and rutting has been developed. It has been proved that the structural model of Burgers does not fully meet all the requirements of the asphalt-concrete.
ВЯЗКОУПРУГАЯ СТРУКТУРНАЯ МОДЕЛЬ АСФАЛЬТОБЕТОНА
В’ЯЗКОПРУЖНА СТРУКТУРНА МОДЕЛЬ АСФАЛЬТОБЕТОНУ
Keywords: viscoelasticity; Kelvin model; Hooke element; Newton element; stress tensor; strain tensor; вязкоупругость; модель Кельвина; элемент Гука; элемент Ньютона; тензор напряжений; тензор деформаций; в’язкопружність; модель Кельвіна; елемент Гука; елемент Ньютона; тензор напружень; тензор деформацій; 625.8.06